PECULIARITIES OF PSYCHOSOCIAL MALADJUSTMENT IN WOMEN RAISING CHILDREN WITH MENTAL AND PHYSICAL DISABILITIES - Sedykh, K.V.; Shevchuk, S.M.; Shevchuk, V.V.; Klymenko, Y.O. (World of Medicine and Biology, 2020)
Theoretical study of scientific sources allowed to define the concept of "child with mental and physical disabilities", their classification and generalize views on the phenomenon of maladaptation. An empirical study of psychosocial maladjustment of women raising children with mental and physical disabilities involved 274 mothers who have children of different ages with developmental disorders. The study lasted from June 2018 to March 2019 in the Podilsky district of Poltava, where 110 women were interviewed, in Lubny and Lubny district – 112 women and Kozelshchyna district of Poltava region – 52 women. Based on the analysis of the obtained results, it was found that in urban localities the number of mothers with signs of psychological maladjustment is lower (in Podilsky district of Poltava – 56-61%, in Lubny and Lubny district –72.5-73%) than in rural areas (in Kozelshchyna district – 91–95%).
Keywords: psychosocial adaptation; psychological maladaptation; child with limited mental and physical abilities